MATHEMATICS LEARNING ACHIEVEMENT: DISCOVERY LEARNING COLLABORATION THINK PAIR SHARE VIEWED FROM REASONING - Anggoro Yugo Pamungkas; Sugiman Sugiman; Nining Setyaningsih (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to (1) analyze Discovery Learning Setting Think Pair Share on mathematics learning achievement, (2) analyze the level of students 'reasoning towards mathematics learning achievement, and (3) determine the interaction of Discovery Learning Setting Think Pair Share and the level of students' reasoning on mathematics learning achievement. This type of research uses quantitative research with a quasi-experimental design. All grade VIII students of State Junior High School 1 Sambi were the population of this study. The sample in this study consisted of two classes, 31 experimental and 32 control students, with a sampling technique using cluster random sampling. Data collection techniques using documentation, tests, and questionnaires. The data analysis technique used the ANOVA technique. Two ways with different cells. The results of the study with a significance level of 5% are (1) there is a good effect using Discovery Learning Setting Think Pair Share on students 'mathematics learning achievement, (2) there is a good effect of reasoning on students' mathematics learning achievement, and (3) there is no interaction between Discovery Learning. Think Pair Share setting and students' reasoning. Therefore, it is concluded that mathematics learning achievement can be influenced by Discovery Learning Setting Think Pair Share and reasoning. Keywords: Discovery learning setting think pair share; mathematics learning outcomes; reasoning. AbstrakPenelitian ini bertujuan untuk (1) menganalisis Discovery Learning Setting Think Pair Share terhadap prestasi belajar matematika, (2) menganalisis tingkat penalaran siswa terhadap prestasi belajar matematika, dan (3) mengetahui interaksi Discovery Learning Setting Think Pair Share dan tingkat penalaran siswa terhadap prestasi belajar matematika. Jenis penelitian menggunakan penelitian kuantitatif dengan desain quasi experiment. Seluruh siswa kelas VIII SMP Negeri 1 Sambi menjadi populasi penelitian ini. Sampel dalam penelitian ini terdiri dari dua kelas dengan 31 siswa eksperimen dan 32 siswa kontrol, dan pengambilan teknik sampling menggunakan cluster random sampling. Teknik pengumpulan data menggunakan metode dokumentasi, tes dan angket. Teknik analisis data menggunakan teknik ANAVA dua jalan dengan sel tak sama. Hasil penelitian dengan tingkat signifikansi 5% adalah (1) ada pengaruh baik menggunakan Discovery Learning Setting Think Pair Share terhadap prestasi belajar matematika siswa, (2) ada pengaruh baik penalaran terhadap prestasi belajar matematika siswa, dan (3) tidak ada interaksi antara Discovery Learning Setting Think Pair Share dan penalaran siswa. Oleh karena itu, disimpulkan bahwa prestasi belajar matematika dapat dipengaruhi oleh Discovery Learning Setting Think Pair Share dan penalaran. Kata Kunci: Discovery learning setting think pair share; penalaran; prestasi belajar matematika.